Legal Analysis of Criminal Responsibility of Perpetrators of Theft Crimes (Study of Decision Number: 662/Pid.B/2024/PN Jkt.Pst) - Makmaker, Petronela Yosinta Kelyombar; Hafidz, Jawade (UNISSULA Semarang, 2025)
This study entitled